IDENTIFIKASI TOTAL MIKROBA, CEMARAN Escherichia coli DAN NILAI pH SUSU PASTEURISASI YANG BEREDAR DI KOTA MALANG - Oktavia Rahayu Puspitarini; Nurul Jadid Mubarakati (JURNAL ILMIAH PETERNAKAN TERPADU, 2019)
Malang is a rich culinary city of livestock products such as pasteurized milk. The purposes of this study were analyzed total microbes, contamination of Escherichia coli and pH of pasteurized milk produced by milk store, village unit cooperation milk house and STMJ cafe in Malang. The method of this research were survey and experiment. The samples were took from milk store (P1), village unit cooperation milk house (P2) and STMJ café (P3)  in Malang during 4 days. The data analysis of total microbial and pH using one-way analysis of variance (ANOVA) and continued by Duncan Multiple Range Test (DMRT) while Escherichia coli data was analyzed by descriptive analysis. The results showed that there were a real influence (P<0,05) of milk producers on total microbes and pH. Escherichia coli contaminant from three producers were showed the same results which were less than 3 apm/ml. The conclusions of this study were total microbes and contamination of Escherichia coli original pasteurized milk produced by milk store, village unit cooperation milk house and STMJ cafe under the limit of microbial contamination on food. Microbiological quality in terms of total microbes, and contamination of Escherichia coli pasteurized milk by milk store in Malang City were classified to national standard of pasteurized milk in Indonesia. Keywords: Total Microbes, Escherichia coli, pH, Pasteurized Milk, Malang City